The Role of Mentor Facilitators in MSME Capacity Development and Sustainability - Achmad Babun Najih; Fauzan Fauzan (Research Horizon, 2026)
MSMEs are a key pillar of the national economy, contributing significantly to employment and economic growth in Indonesia. However, MSMEs, particularly productive, underprivileged women in rural areas, still face various limitations, such as low entrepreneurial literacy, market access, and technological mastery. This study aims to analyze the role of mentor facilitators in the development of MSMEs belonging to customers and their impact on increasing business capacity and sustainability. The study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results show that mentor facilitators play a strategic role as educators, motivators, mediators, and business mentors. Mentoring has a positive impact on increasing entrepreneurial knowledge, business management, marketing, and business identity awareness. However, obstacles remain, such as limited customer digital literacy and limited mentoring materials. This study recommends strengthening the mentoring curriculum based on local needs and improving digital literacy to encourage MSMEs to move up the ranks sustainably.